THE EFFECT OF EDUCATIONAL GAME ON STRESS LEVEL OF PRE-SCHOOL CHILDREN AFTER KELUD MOUNTAIN DISASTER - . Adiyanto; . Muarrofah; . Baderi (STIKES Insan Cendekia Medika Jombang, 2011)
Childhood is golden period. Where pre school children experienced physical stress, emotions, thoughts and behaviors caused by various causes and sources such as disaster with concentration symptom, anxiety and fear. Pre-school children generally were cooperative in making game. The purpose of this study was to analyze the effect of educational game on stress level of pre-school children after Kelud mountain disaster.The design of this study used